2000
DOI: 10.1006/viro.1999.0080
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus EP153R Open Reading Frame Encodes a Glycoprotein Involved in the Hemadsorption of Infected Cells

Abstract: The open reading frame EP153R, located within the EcoRI E' fragment of the African swine fever (ASF) virus genome, is predicted to encode a membrane protein of 153 amino acids that presents significant homology to the N-terminal region of several CD44 molecules. EP153R contains multiple putative sites for N-glycosylation, phosphorylation, and myristoylation, a central transmembrane region, a C-type animal lectin-like domain, and a cell attachment sequence. Transcription of EP153R takes place at both early and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 31 publications
1
50
0
2
Order By: Relevance
“…pA224L inhibited caspase activity and cell death induced by various means when stably overexpressed in Vero cells, an effect likely resulting from the direct interaction of pA224L with the catalytic fragment of caspase-3 (Nogal et al 2001). Caspase-3 activity is also affected by ASFV pEP153R, a C-type lectin-like protein expressed throughout the infectious cycle (Galindo et al 2000a;Yanez 1995). Increased levels of caspase-3 and apoptosis occurred in cells infected with ASFV mutants lacking EP153R (Hurtado et al 2004).…”
Section: Viral Modulation Of Apoptosismentioning
confidence: 98%
“…pA224L inhibited caspase activity and cell death induced by various means when stably overexpressed in Vero cells, an effect likely resulting from the direct interaction of pA224L with the catalytic fragment of caspase-3 (Nogal et al 2001). Caspase-3 activity is also affected by ASFV pEP153R, a C-type lectin-like protein expressed throughout the infectious cycle (Galindo et al 2000a;Yanez 1995). Increased levels of caspase-3 and apoptosis occurred in cells infected with ASFV mutants lacking EP153R (Hurtado et al 2004).…”
Section: Viral Modulation Of Apoptosismentioning
confidence: 98%
“…This ASFV protein is required for the hemadsorption (HAD) of red blood cells around ASFV-infected cells and also for the association of extracellular virions with red blood cells (5,23,26). One report showed that deleting the ORF EP153R, which encodes a C-type lectin, reduced the numbers of red blood cells binding to infected cells, suggesting that EP153R was also involved in HAD (13). Although most isolates of ASFV cause HAD, some field isolates that are non-HAD have been characterized, and these include both virulent and nonvirulent isolates (4,20,30).…”
mentioning
confidence: 99%
“…The principal exception to this is the product of the EP402R gene, which is a viral homologue of CD2 and, in conjunction with the product of the EP135R gene, recruits erythrocytes to infected cells. This may sterically mask virally infected cells from cytotoxic white blood cells (5,12,33). ASFV also encodes an inhibitor of nuclear factor B (NF-B) and nuclear factor of activated T cells, which can repress proinflammatory immune responses (25,29,36).…”
mentioning
confidence: 99%